2015
DOI: 10.1186/s12912-015-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

Students’ understanding of “Women-Centred Care Philosophy” in midwifery care through Continuity of Care (CoC) learning model: a quasi-experimental study

Abstract: BackgroundThe philosophy of midwifery education is based on the ‘Women-centred care’ model, which provides holistic care to women. Continuity of care (CoC) is integral to the concept of holistic women-centred care and fundamental to midwifery practice. The objective of this study was to determine any differences in students’ understanding of midwifery care philosophy between students who underwent the CoC learning model and those who underwent the fragmented care learning model.MethodWe used a quasi-experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 18 publications
1
30
0
13
Order By: Relevance
“…The implementation is only additional, not widely understood by pregnant women, and only focuses on physical preparation to the face of childbirth (16)(17)(18)(19). Whereas currently midwifery practices applied a holistic approach to identified the needs of women as a whole, because health is a harmonization of the physical, mental, and soul (20).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation is only additional, not widely understood by pregnant women, and only focuses on physical preparation to the face of childbirth (16)(17)(18)(19). Whereas currently midwifery practices applied a holistic approach to identified the needs of women as a whole, because health is a harmonization of the physical, mental, and soul (20).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) includes pain management as a standard of quality of care, highlighting that all aspects of health care should be given timely, appropriately, and should respect a woman’s choice, culture and needs [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, there have been various studies mostly in UK and Japan on women-centred care during pregnancy and childbirth [23,25,26,36,[57][58][59][60]. The qualitative and quantitative results of a previous survey of expectant and nursing mothers done in the UK indicated that there is a need for woman-centred care through which midwives form partnerships with expectant and nursing mothers, and help expectant and nursing mothers make information-based choices [61]. Many of our participants were unable to form such partnerships with their local midwives during the perinatal period, consequently were unableto achieve the desired childbirth experience.…”
Section: Woman-centred Carementioning
confidence: 99%